Analysis of relationship between viability of cows, herd turnover rate, and milk production efficiency (system and algorithm modeling) - Cherepanov, G. G; Makar, Z. N (Russian agricultural sciences, 2015)
A model with a simple algorithm is presented to analyze the efficiency of milk production, taking into consideration the viability and productivity of cows, dairy herd turnover rate, and main economic indicators. Principle propositions of a general approach are set forth without any complicated mathematical formulas and equations. The impact of viability on herd profitability and reproductive performance has been analyzed with the actual data on culled Holstein Black-and-White and Holmogorskaya cows. Reducing the culling rate in first lactations should be recognized as a major breeding criterion for extending the average productive lifespan of cows.